Toxic Masculinity: Negative Attitudes Towards Gender-Based Professions - Mutiah Silmi Syarifah; Suryanto Suryanto; Dyan Evita Santi (International Journal of Educatio Elementaria and Psychologia, 2024)
Masculinity is a male characteristic in men which is not externally innate but is shaped by the culture in which one lives. Due to societal stigma, men have to do manly jobs or professions to be seen as complete men. Excessive stigma against traditional masculinity also gives rise to toxic masculinity, which is a social norm that considers how men should behave based on existing standards of traditional masculinity. on local culture. This research aims to analyze the impact and solutions for negative attitudes towards gender-based professions. The method used in this research is a qualitative method with a phenomenological approach. Data were collected through semi-structured interviews with two adult male participants who work across gender. The research results show that the phenomenon of toxic masculinity has an impact on men who are victims of masculinity. However, this can be minimized for victims by developing personal abilities, focusing on goals and getting support from the closest environment.